Wound healing: a new perspective on glucosylated tetrahydrocurcumin - Bhaskar Rao A; Prasad E; Deepthi SS; Haritha V; Ramakrishna S; Madhusudan K; Surekha MV; Venkata Rao YSR (Dove Medical Press, 2015)
Adari Bhaskar Rao,1 Ernala Prasad,1 Seelam Siva Deepthi,1 Vennapusa Haritha,1 Sistla Ramakrishna,1 Kuncha Madhusudan,1 Mullapudi Venkata Surekha,2 Yerramilli Sri Rama Venkata Rao3 1Medicinal Chemistry and Pharmacology Division, Council of Scientific and Industrial Research – Indian Institute of Chemical Technology, 2Pathology Division, National Institute of Nutrition, 3Ashian Herbex Ltd, Hyderabad, AP, India Abstract: Wound healing represents a dynamic set of coordinated physiological processes observed in response to tissue injury. Several natural products are known to accelerate the process of wound healing. Tetrahydrocurcumin (THC), an in vivo biotransformed product/metabolite of curcumin, is known to exhibit a wide spectrum of biological activities similar to those of native curcuminoids. The poor bioavailability of these curcuminoids limits their clinical applications. The present study highlights the percutaneous absorption and wound healing activity of glucosyl-conjugated THC (glucosyl-THC) in male Wistar rats. A high plasma concentration of glucosyl-THC (4.35 µg/mL) was found in rats 3 hours after application. A significant enhanced wound healing activity and reduced epithelialization time were observed in rats that received glucosyl-THC. This may have been due to the improved bioavailability of the glucosyl compound. The nonstaining and lack of skin-sensitive side effects render the bioconjugated glucosyl-THC a promising therapeutic compound in the management of excision wounds and in cosmetic applications, in the near future. Keywords: glucosylation, epithelialization, granulation tissue, cosmetic, therapeutic